Case Report: Novel ATP13A2 pathogenic variants associated with early-onset parkinsonism and a mini-review - Affronte, Leonardo; Pini, Antonella; Pizzoli, Claudia; Coccia, Emanuele; Mazzone, Serena; Golemi, Arber; Giannotta, Melania; Cordelli, Duccio Maria; Carelli, Valerio; Vaisfeld, Alessandro; Palombo, Flavia (Frontiers in Genetics, 2025)
ATP13A2 is a gene localized on chromosome 1p36.13 and coding for a transmembrane protein found in the lysosomes and late endosomes, which is involved in many cellular metabolic activities. Pathogenetic variants of ATP13A2 are associated with a wide range of neurodegenerative disorder including Kufor Rakeb syndrome (KRS), a rare autosomal recessive form of levodopa responsive juvenile onset parkinsonism (MxMD-ATP13A2), characterized by rapidly progressive muscular stiffness, bradykinesia, spasticity, pyramidal findings, dementia and supranuclear gaze palsy. The aim of this study is to provide detailed clinical descriptions of two siblings, carriers of novel biallelic ATP13A2 variants. One of them showed KRS levodopa-responsive motor dystonic features at the age of 10 years preceded by moderate cognitive impairment, while the other only showed mild cognitive impairment at our last evaluation at 11 years of age. Additionally, we reviewed the previously published cases, focusing on early signs and symptoms, clinical evolution and response to therapy. To our knowledge, this is the only work that groups all reported KRS patients and compares their clinical and molecular features.